Najważniejsze to kochać... kino! Miłość i kinofilia w filmie Andrzeja Żuławskiego - Maron, Marcin (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2024)
The article concerns the legendary French film by Andrzej Żuławski entitled Najważniejsze to kochać! [The Most Important Thing: Love!] (1975) starring: Romy Schneider, Fabio Testi and Jacques Dutronc. The author discusses three main topics in the film: in the first part: issues of love and the metaphysical evil; in the second part: the very rich context of literary and film references. Andrzej Żuławski shows love as a force leading to the protagonists’ moral change and, at the same time, the incessant, unsatiable urge, resulting from human imperfection. In Żuławski’s film, as in the novels by Fyodor Dostoyevsky, the experience of love is connected with human duality, as well as with the contradictions appearing between the pole of love-desire and the pole of love-compassion. The duality of love results from the evil inherent in the nature of the world. According to Żuławski, evil is an active force acting in the world and not only a “lack of good.” The protagonists, experiencing evil, cross the existential and cognitive threshold and their experiences become closer to Gnostic experiences (gnosis). In the second part the author thoroughly discussed the French and international context of production and accomplishment of the film Najważniejsze to kochać. He indicated numerous literary references, co-creating the sense of the film (Shakespeare, Dostoyevsky, romantic literature) and cinema (commercial cinema: C. Sautet, A. Kurosawa, L. Olivier, J. von Sternberg, J.-L. Godard) proving that Żuławski’s film is the expression of the specific love for the cinema, i.e. cinemaphilia. The indicated references also co-create the ironic manner of representing the world presented in the film, where the motif of the actors’ acting becomes important, as well as that of life as theatre and masks, behind which people hide their intentions and emotions.